Transparent Electrodes Fabricated from Single Walled Carbon Nanotubes and Ni Nanoparticles with Low Contact Resistance to p-Al0.3Ga0.7N. (28th November 2018) - Park, Jun-Beom; Rho, Hokyun; Bae, Hyojung; Chung, Tae Hun; Jeong, Tak; Ha, Jun-Seok
Abstract : The transparent conductive electrodes (TCEs) that have high-transmittance in the ultra-violet region are reported. The TCEs in this paper consist of combination of single-walled carbon nanotubes (SWCNTs) and nanoscale Ni particles (Ni NPs). TCEs can form low-resistance by directly contacting to p-AlGaN without ohimic contact layer of p-GaN that absorbed light energy in the UV region. Ni NPs are combined on the surface of the SWCNTs to enhance the work function, resulting in the low contact resistance between TCEs and p-Al0.3 Ga0.7 N. And, the specific contact resistance of TCEs and p-Al0.3 Ga0.7 N is 8.97 × 10 −2 Ωcm, 2 which means that it is possible to improve the output power of light emitting diodes by directly forming TCEs on p-AlGaN without inserting p-GaN layer.